Autonomous Assembly as the Fourth Approach to Generic Construction. (July 2017) - Lu, Andong
Abstract : The three major approaches to generic construction tested since the advent of prefabrication – element assemblage, layer stratification and module composition – all maintain a separation between manufacturing and assembly. Autonomous assembly, in contrast, coalesces these into a single method of collective production. But – as Andong Lu, Professor at the School of Architecture and Urban Planning, Nanjing University, argues – for such innovative approaches to inspire the future of architecture, it is crucial to connect technology, design and people, based on a comprehensive understanding of construction.